2019
DOI: 10.7567/1347-4065/ab4481
|View full text |Cite
|
Sign up to set email alerts
|

Phase-resolved profiles of electron energy deposition in inductively coupled radio-frequency plasmas driven under confronting divergent magnetic fields

Abstract: File InformationNakashima-JJAP-58(11)-116001-HUSCAP.pdf Hokkaido University Collection of Scholarly and Academic Papers : HUSCAP Typeset with jjap2.cls

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The chamber is a cylinder with a 40.0 cm inner diameter and a 40.0 cm height as assumed in previous work. 11,17,19) The origin of position (x, y, z) in a Cartesian coordinate or (r, θ, z) in a cylindrical coordinate is the center of the chamber. Here, r is the radial position, z is the axial position, and θ is the azimuthal angle.…”
Section: Chamber Dimensions and Coordinatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The chamber is a cylinder with a 40.0 cm inner diameter and a 40.0 cm height as assumed in previous work. 11,17,19) The origin of position (x, y, z) in a Cartesian coordinate or (r, θ, z) in a cylindrical coordinate is the center of the chamber. Here, r is the radial position, z is the axial position, and θ is the azimuthal angle.…”
Section: Chamber Dimensions and Coordinatesmentioning
confidence: 99%
“…16) It was reported that electrons under the CDMFs obtain energy near the B ECR region via a stochastic process. 11,[17][18][19] A notable feature is that the partial resonance may occur even in the region distant from the RF antenna. Although it is considered in general that magnetic field induces the magnetic cooling of the electron temperature by binding the electron motion, the partial resonance is an interesting phenomenon as a mechanism of energy supply to electrons, and it may assist the sustainment of the magnetized ICPs.…”
Section: Introductionmentioning
confidence: 99%
“…81) The azimuthal velocity of electron motion in a cylindrical chamber under an RF electric field and confronting divergent magnetic fields was simulated to evaluate the phase-resolved profiles of power deposition on electrons in a low-pressure inductively coupled magnetized plasma. 82) The average velocity of electron motion under crossed fields of alternative current (AC) electric and DC magnetic components was formulated analytically. The velocity vector draws elliptical loci with alternating electric fields.…”
Section: 5mentioning
confidence: 99%
“…Phase-resolved EEG distribution was observed to analyze the causes of high EEG in several regions in the X-point plasmas. 10,27 It was indicated that a specific configuration of electric and magnetic fields induced a directionality of electron drift and an asymmetric power deposition between the first and second halves of an rf period. In the vicinity of the sidewall of the chamber, it was revealed that a directionality caused by electron reflection under a magnetic field leads to a stochastic EEG.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] We focus on the plasma flow controllability through the adjustment of coil currents inducing the magnetic fields. 9,10) The magnetic fields are expected as magnetic filter/shutter, [11][12][13][14][15][16][17][18][19][20][21][22] and their potential applications would be advanced plasma modulation and downsizing of remote plasmas. On the other hand, it is known that magnetic fields have cooling effect on electrons in plasmas.…”
Section: Introductionmentioning
confidence: 99%